ปัจจัยทำนายกลุ่มอาการของผู้ที่เป็นโรคปอดอุดกั้นเรื้อรัง - พัชรินทร์ คำแก่น (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Chronic obstructive pulmonary disease (COPD) is one of the most common respiratoryproblemswhich can leadtosymptom clusterings. COPDaffects one’sphysical, mental, emotional, and social health. The purpose of this study was to explore factors predicting symptom clusters among persons with COPD. These factors included lung function, nutritional status, smoking patterns, perceived self-efficacy, and perceived social support. A sample of 152 adults with COPD aged 45-65 years old was recruited from ChiangraiPrachanukroh HospitalandMaechan Hospital. Research instruments used for data collection consisted of a Demographic Data Recording Form, Symptom Cluster Questionnaire, Perceived Self-Efficacy Questionnaire, and Perceived Social Support Questionnaire. Content validity of all instruments was judged by a panel of experts. The reliability of the questionnaires were also tested and each questionnaire was at an acceptable level. Data were analyzed by using descriptive statistics and multiple regression. The result revealed that: Factors that were statisticallysignificant correlated with symptom clusters weremoderate level of perceived social support (r = .35, p <.01), nutritional status (underweight) (r = .28, p < .01), moderate level of perceivedself-efficacy (r = .20, p < .05) and low level ofperceivedself-efficacy (r = .18,p < .05) Factors that predicted symptom clusters werenutritional status (underweight), lowand moderate level of perceivedself-efficacyandmoderate level ofperceived social support.These factors accounted for 26 % (p < .001) of symptom clusters among persons with COPD. The results from the study provides datafor nurses in improving care of COPD patients by promoting nutritional status in the patients who areunderweight, as well as enhancing self-efficacy andsocial support inorder to decrease perception of symptom clusters. Moreover, the study results can be used asbaseline data for further research related to management of symptom clusters among COPD patients.